2022
DOI: 10.1186/s12905-022-01814-x
|View full text |Cite
|
Sign up to set email alerts
|

“It’s only fatness, it doesn’t kill”: a qualitative study on perceptions of weight gain from use of dolutegravir-based regimens in women living with HIV in Uganda

Abstract: Background Dolutegravir (DTG)-based regimens have been recommended by the WHO as the preferred first-line and second-line HIV treatment in all populations. Evidence suggests an association with weight gain, particularly among black women. Our study investigated perceptions of weight gain from DTG-based regimen use on body image and adherence of antiretroviral therapy in women living with HIV (WLHIV) in Uganda. Methods Between April and June 2021, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Qualitative research among women with HIV in Uganda found that weight gain with TLD was rarely perceived as an adverse event and would be unlikely to alter adherence [17]. Our analysis provides some quantitative support for these observations.…”
Section: Discussionsupporting
confidence: 63%
“…Qualitative research among women with HIV in Uganda found that weight gain with TLD was rarely perceived as an adverse event and would be unlikely to alter adherence [17]. Our analysis provides some quantitative support for these observations.…”
Section: Discussionsupporting
confidence: 63%
“…Lastly, we did not analyze the impact of different ART regimens on BMI, as almost all patients were on an efavirenz-based first-line regimen. Dolutegravir, which has been reported to be associated with weight gain [15,[44][45][46][47][48], has only relatively recently been rolled out in Tanzania. Future studies are planned to assess the impact of dolutegravir on BMIs in this population and the current study will set a baseline to be compared with the dolutegravir-based ART regimen.…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, weight gain should be universally reported in association with INSTI use. Weight gain may be under-reported in underdeveloped areas due to positive perceptions of weight gain, leading to inefficient risk communication to HIV patients experiencing unhealthy weight gain [109].…”
Section: Weight Gainmentioning
confidence: 99%